2007
DOI: 10.1111/j.1600-051x.2007.01149.x
|View full text |Cite
|
Sign up to set email alerts
|

Does tooth brushing influence the development and progression of non‐inflammatory gingival recession? A systematic review

Abstract: Aim: The aim of this systematic review was to produce the best available evidence and pool appropriate data to evaluate the effect of tooth brushing on the initiation and progression of non-inflammatory gingival recession. Material and Methods: A protocol was developed a priori for the question: ''Do factors associated with tooth brushing predict the development and progression of non-inflammatory gingival recession in adults?'' The search covered six electronic databases between January 1966 and July 2005. Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
122
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(137 citation statements)
references
References 77 publications
7
122
0
8
Order By: Relevance
“…However, it may be speculated that the participants had inadequate knowledge to perform effective tooth cleaning procedures as it has also been reported that poor skills for toothbrushing were very much evident among primary school teachers (34). In this study, the frequency of toothbrushing did not appear to have been a significant factor for the occurrence of gingival recession and this is in agreement to what has been reported in Jordan (35) and other places (36).…”
Section: Discussionsupporting
confidence: 80%
“…However, it may be speculated that the participants had inadequate knowledge to perform effective tooth cleaning procedures as it has also been reported that poor skills for toothbrushing were very much evident among primary school teachers (34). In this study, the frequency of toothbrushing did not appear to have been a significant factor for the occurrence of gingival recession and this is in agreement to what has been reported in Jordan (35) and other places (36).…”
Section: Discussionsupporting
confidence: 80%
“…The patients rinsed their mouths with 0.12% chlorhexidine gluconate every 12 h for 3 days. [23][24][25] All patients underwent presurgery prophylaxis as described above.…”
Section: Methodsmentioning
confidence: 99%
“…In the marginal area, the use of an abrasive dentifrice (RDA = ± 160) significantly increased the incidence of abrasion, regardless of the toothbrush t ype used. Although the evidence to confirm the relationship between traumatic toothbrushing and gingival recession are inconclusive, 6,29 the majority of studies verify this association.…”
Section: Discussionmentioning
confidence: 99%